Metal‐Free and Visible‐Light‐Promoted C‐3 Thiocyanation of 2‐Arylquinolin‐4‐ones. Issue 27 (28th June 2019) - Chauhan, Parul; Ritu,; Preeti,; Kumar, Sharvan; Jain, Nidhi
Abstract : A C‐3 thiocyanation of 2‐aryl‐quinolin‐4‐ones in the presence of eosin‐Y and visible light has been developed. The methodology allows easy access to a variety of 2‐aryl‐3‐thiocyano‐quinolin‐4‐ones in moderate to high yields. Regioselective para ‐thiocyanation of anilines has also been achieved under these conditions. The reaction is operationally simple, metal‐free, requires air as the oxidant, and proceeds smoothly at room temperature. Abstract : A visible‐light‐mediated regioselective thiocyanation of quinolones and anilines has been accomplished with ammonium thiocyanate in the presence of eosin‐Y under irradiation with a blue LED. The reaction conditions are mild, metal‐free, economical, and moderate to high product yields are obtained.